2017
DOI: 10.1002/mp.12483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respiratory motion and acquisition settings on SPECT liver dosimetry for radioembolization

Abstract: Respiratory motion has a large effect on SPECT activity quantitation of liver tumors as used in radioembolization treatment planning and assessment. As compared with the other parameters that were varied in this study, respiration is the predominant degrading effect on image quantitation. Gating alleviates much of this detrimental effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 52 publications
(104 reference statements)
3
29
2
1
Order By: Relevance
“…Bastiaannet et al. demonstrated that respiration is the predominant degrading effect on 90 Y SPECT image quantification and can be alleviated through respiratory gating 25. A similar conclusion was presented by Siman et al.…”
Section: Discussionsupporting
confidence: 78%
“…Bastiaannet et al. demonstrated that respiration is the predominant degrading effect on 90 Y SPECT image quantification and can be alleviated through respiratory gating 25. A similar conclusion was presented by Siman et al.…”
Section: Discussionsupporting
confidence: 78%
“…In the current protocol, patient breathing was not accounted for. Patient breathing is known to result in an underestimation of actual activity depositions and blur SPECT/CT images [20]. This issue may be resolved by applying breath gating during image acquisition, although this feature is currently not supported on our SPECT/CT imaging devices.…”
Section: Discussionmentioning
confidence: 99%
“…8b) and tumor ( Fig. 8a) VOIs were determined on SPECT images by setting a threshold such that the volume of VOIs equaled to that of corresponding VOIs from the contrast HCT-EX image [26]. The tumor and NL VOIs obtained from these methods can then be used to calculate TNR using Eq.…”
Section: Tnr Estimationmentioning
confidence: 99%